Intelligent Computational Paradigms in Earthquake Engineering - Lagaros (Nikos D); Tsompanakis (Yiannis) ("70/E, Chocolate Avenue - Suite 200 Hershey, PA 17033,USA", 2007)
Earthquake
22.5
Keywords: Earthquake